Rapid Chloride Permeability Studies on High Strength Concrete with Nano Al2o3 and Silica Fume - B. Ajitha, H. Sudarsana Rao (International Journal of Advanced Science and Technology, 2020)
The quality of a structure plays major role for the safety of assets and also its durability. Deterioration of structure mostly occurs due to the failure in reinforcement this is seen most commonly in present days. Thus, increases the concentration of durability of the structure. Maintaining the damaged structure and making it durable is a costly method. Environmental impact on reinforcement makes the steel to corrode.This is formed by the diffusion of chloride into the concrete structure. The chlorine ion can induce into the concrete by different mechanisms such as capillary action, diffusion and hydrostatic pressure. Maximum chloride is induced by diffusion technique. Diffusion is a process in which the concentration of chlorine is transferred from higher to lesser that is from outside to inside till the reinforcement. The concentration of diffusion depends on the porosity of concrete structure. The Porosity of hardened concrete depends on hydration, curing, replacement of materials.High strength concrete (HSC) is a concrete shows higher performance. This is done by introducing admixtures such as silica fume, nano aluminium oxide, super plasticizer which increases the properties of concrete. Mineral admixture introduces favorable behavior with respect to shrinkage and high development of heat of hydration and enhances durability. Low water/cement ratio is a crucial aspect which can be achieved by using chemical admixtures such as super plasticizer. This study deals with M60 grade of plain cement concrete contains different percentages of silica fume and nano Al2O3 by weight of cement. Experimental investigations are carried out with cylindrical specimen of 100mm x 150mm is casted with varying percentage of Silica fume of 0, 5, 15, 20 and 25% and nano Al2O3 of 0, 0.5 ,1 and 1.5%. Rapid chloride permeability test has been conducted on all these mixes with a curing period of 28, 60 and 90 days as a measure of durability and the results are presented. Keywords: Nano Al2O3, silica fume, rapid chloride permeability test.